Early echocardiographic alterations in cancer patients during chemotherapy - Z. Z.A. Fashafsha; P. Sh. Chomakhidze; D. F. Mesitskaya; A. Yu. Suvorov; M. I. Sekacheva; E. V. Poddubskaya; E. S. Tyukanova; M. V. Sankova; M. A. Ozova; V. D. Levina; D. А. Andreev; F. Yu. Kopylov (Российский кардиологический журнал, 2022)
Aim. To evaluate the early manifestation of cardiotoxicity after the first course of multiagent chemotherapy (MAC) using echocardiography with an assessment of the left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS).Material and methods. The study included 49 cancer patients with elective MAC.Results. After the first administration of a therapeutic dose of chemotherapy, a decrease in LVEF ≥10 and GLS >15 was demonstrated in more than 6,1% of patients, as well as a subclinical decrease in LVEF ≥5% in 22,4% and a decrease in GLS ≥12% in 24,5%.Conclusion. In cancer patients, after the first course of chemotherapy, GLS dynamics should be assessed during echocardiography as a marker of myocardial dysfunction.